Pressure Overload Activates DNA-Damage Response in Cardiac Stromal Cells: A Novel Mechanism Behind Heart Failure With Preserved Ejection Fraction? - Stadiotti, Ilaria; Santoro, Rosaria; Scopece, Alessandro; Pirola, Sergio; Guarino, Anna; Polvani, Gianluca; Maione, Angela Serena; Ascione, Flora; Li, Qingsen; Delia, Domenico; Foiani, Marco; Pompilio, Giulio; et al. (Frontiers in Cardiovascular Medicine, 2022)
Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous syndrome characterized by impaired left ventricular (LV) diastolic function, with normal LV ejection fraction. Aortic valve stenosis can cause an HFpEF-like syndrome by inducing sustained pressure overload (PO) and cardiac remodeling, as cardiomyocyte (CM) hypertrophy and fibrotic matrix deposition. Recently, in vivo studies linked PO maladaptive myocardial changes and DNA damage response (DDR) activation: DDR-persistent activation contributes to mouse CM hypertrophy and inflammation, promoting tissue remodeling, and HF. Despite the wide acknowledgment of the pivotal role of the stromal compartment in the fibrotic response to PO, the possible effects of DDR-persistent activation in cardiac stromal cell (C-MSC) are still unknown. Finally, this novel mechanism was not verified in human samples. This study aims to unravel the effects of PO-induced DDR on human C-MSC phenotypes. Human LV septum samples collected from severe aortic stenosis with HFpEF-like syndrome patients undergoing aortic valve surgery and healthy controls (HCs) were used both for histological tissue analyses and C-MSC isolation. PO-induced mechanical stimuli were simulated in vitro by cyclic unidirectional stretch. Interestingly, HFpEF tissue samples revealed DNA damage both in CM and C-MSC. DDR-activation markers γH2AX, pCHK1, and pCHK2 were expressed at higher levels in HFpEF total tissue than in HC. Primary C-MSC isolated from HFpEF and HC subjects and expanded in vitro confirmed the increased γH2AX and phosphorylated checkpoint protein expression, suggesting a persistent DDR response, in parallel with a higher expression of pro-fibrotic and pro-inflammatory factors respect to HC cells, hinting to a DDR-driven remodeling of HFpEF C-MSC. Pressure overload was simulated in vitro, and persistent activation of the CHK1 axis was induced in response to in vitro mechanical stretching, which also increased C-MSC secreted pro-inflammatory and pro-fibrotic molecules. Finally, fibrosis markers were reverted by the treatment with a CHK1/ATR pathway inhibitor, confirming a cause-effect relationship. In conclusion we demonstrated that, in severe aortic stenosis with HFpEF-like syndrome patients, PO induces DDR-persistent activation not only in CM but also in C-MSC. In C-MSC, DDR activation leads to inflammation and fibrosis, which can be prevented by specific DDR targeting.